Ultrafast dynamics of excitonic scattering and gain in narrow ZnCdSe/ZnSe multiple quantum wells - Hess, S; Taylor, R; Adams, R; Ryan, J; Park, R (1998)
Time-resolved photoluminescence has been used to investigate the optical properties of a narrow 25 Å Zn0.8Cd0.2Se/ZnSe multiple quantum well structure as a function of carrier density and temperature. At low temperatures, it is found that the luminescence is excitonic over all densities up to and above threshold. The underlying gain mechanism in cleaved 380 μm cavities is excitonic in nature. In the low-density regime, the luminescence remains excitonic up to room temperature. © 1998 Elsevier Science B.V. All rights reserved.